Le nu et le vêtu dans l’Histoire d’un voyage faict en la terre du Brésil de Jean de Léry - Frank Lestringant (Viatica)
This study is a commentary on chapter VIII of Jean de Léry’s Histoire d’un voyage faict en la terre du Brésil (p. 210-236), devoted to the « naturalness, strength, stature, nudity » of the Tupinamba Indians allied with the French. Centered on nudity, firmly underlined by Léry, it offers a gallery of full-length portraits, beginning with the adult, male then female, and ending with the children. Such is the paradox of an ornate bodily nudity, displaying a great variety of adornments, and contradicting the severe censures of contemporaries like the pastor Lambert Daneau. The nude, in the end, is itself a garment, varied to the extreme according to the individuals and the circumstances. It goes hand in hand with humor and verbal play.